2022
DOI: 10.3389/fpsyg.2022.914682
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chinese EFL Students’ Academic Engagement: The Impact of L2 Enjoyment and Academic Motivation

Abstract: Students’ personal, emotional, and psychological traits are perceived to be highly influential in their academic engagement; therefore, many investigations have been conducted into the role of students’ characteristics in their level of engagement. Yet, the role of L2 enjoyment and academic motivation as two instances of students’ emotional traits was disregarded. To narrow this gap, this article aimed to assess the effects of these two constructs on Chinese EFL students’ academic engagement. To accomplish thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
3
29
0
1
Order By: Relevance
“…Due to the vital role that L2 engagement may serve in raising students' learning outcomes (Jarvela & Renninger, 2014;Philp & Nakamura, 2017), identifying the antecedents of this variable sounds critical. To answer this necessity, educational scholars have conducted several investigations into the role of students' personal resources like emotional intelligence, self-efficacy, academic motivation, autonomy, academic buoyancy, and academic self-concept in their L2 engagement (e.g., Beri & Stanikzai, 2018;Ghelichli et al, 2020;Schnitzler et al, 2021;Thomas & Allen, 2021;Wang, 2022;Yuan & Kim, 2018, among others). Further, with the advent of -Positive Psychology (PP)‖, many research studies have considered the role of positive communication behaviors in students' L2 engagement (e.g., Amiryousefi et al, 2019;Derakhshan, 2021;Estepp & Roberts, 2015, among others).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the vital role that L2 engagement may serve in raising students' learning outcomes (Jarvela & Renninger, 2014;Philp & Nakamura, 2017), identifying the antecedents of this variable sounds critical. To answer this necessity, educational scholars have conducted several investigations into the role of students' personal resources like emotional intelligence, self-efficacy, academic motivation, autonomy, academic buoyancy, and academic self-concept in their L2 engagement (e.g., Beri & Stanikzai, 2018;Ghelichli et al, 2020;Schnitzler et al, 2021;Thomas & Allen, 2021;Wang, 2022;Yuan & Kim, 2018, among others). Further, with the advent of -Positive Psychology (PP)‖, many research studies have considered the role of positive communication behaviors in students' L2 engagement (e.g., Amiryousefi et al, 2019;Derakhshan, 2021;Estepp & Roberts, 2015, among others).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that student engagement in the classroom is key to successful learning achievement, studies have assessed whether enjoyment helps students engage in FL classroom activities. For example, Wang (2022) found that Chinese EFL learners' perceived enjoyment was positively correlated with their academic engagement levels and learning achievements. In addition, students' academic motivation played a pivotal role in influencing their academic achievements (ibid.).…”
Section: Enjoyment In Relation To Fl Learningmentioning
confidence: 99%
“…Academic motivation, as Wen ( 2022 ) mentioned, also prompts L2 learners to do their utmost to acquire the second language. Likewise, Wang ( 2022 ) declared that academic motivation pushes L2 learners to invest a huge amount of time, energy, and attempt in mastering the target language.…”
Section: Introductionmentioning
confidence: 99%